Shaping women's work : gender employment and information technology - Webster, Juliet (Harlow, 1996)
"Juliet Webster's book is the fifth title in the Longman Sociology Series of undergraduate texts which combines theoretical debates and empirical research in an accessible way. Webster's book covers the issue of technology and gender relations at work offering a novel approach to the ways in which gender relations shape the design, development and implementation of technologies and how gender relations are also shaped by technologies themselves. Gender and technology, in other words, are 'mutually constitutive' and this argument is developed in the opening chapter of the book. Reviewing the theoretical literature on women's work and technology, Webster opts for a 'social constructionist' view of technology which emphasises that technology is not just about physical artifacts but the product of human knowledge and human activities as well. She combines it with a feminist perspective by locating women's relationship to technology in the context of patriarchal and capitalist relations which have historically excluded women from information technology and this exclusion has been reproduced in contemporary work and employment. Webster's position is clearly expressed against the backdrop of a thorough review of women, employment and technology which students will find invaluable."